Variables Determining Muzaki Loyalty in Paying Zakat, Infaq and Shodaqoh at Zakat Institutions in Indonesia - Ahmad Roziq; Eka Desy Suryaningsih; Nur Hisyamuddin (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
This study aims to find out, test and analyze: (a) the effect of transparencyon muzaki beliefs; (b) the effect of transparency on muzaki loyalty; (c) theeffect of accountability on muzaki’s trust; (d) the effect of accountabilityon muzaki loyalty; (e) the effect of trust on muzaki loyalty in paying zakat,infaq, and almsgiving at the Amil Zakat Institution in Indonesia. This type ofresearch is explanatory research and using survey method. Data collectiontechnique used was questionnaire containing written questions answeredby respondents, namely muzaki (payer of zakat, infaq and sadaqah) at amilzakat institutions. The sampling technique used was purposive sampling,which set the samples based on criteria. The data analysis technique inthis study used the Partial Least Square (PLS) approach. PLS is a modelof Structural Equation Modeling (SEM) based on components or variants.The results of the study found that (a) accountability has a significantpositive effect on muzaki’s trust; (b) transparency has a significant positiveeffect on muzaki’s trust; (c) accountability has a significant positive effecton muzaki loyalty; (d) transparency has a significant positive effect onmuzaki loyalty; (e) trust has a significant positive effect on muzaki loyaltyin paying zakat, infaq, and almsgiving at the Amil Zakat Institutionin Indonesia. The results of this study suggest that zakat managementorganizations increase the loyalty of donors in paying zakat by increasingdonor’s trust by improving transparency and accountability of auditedfinancial reports and in accordance with PSAK 109.